Knights & castles - Dixon, Philip (New York : Simon & Schuster Books for Young Readers, 2007)
Utilizing CGI and 3-D model illustration, this book explores knights and castles.
Keywords: Castles -- Europe -- Knights -- Medieval Civilization -- Feudalism